Verification and validation of CFD simulations for semi-submersible floating offshore wind turbine under pitch free-decay motion. (15th December 2021) - Wang, Yu; Chen, Hamn-Ching; Koop, Arjen; Vaz, Guilherme
Abstract: In this paper a detailed verification and validation study is performed to evaluate the accuracy of CFD simulations for a semi-submersible floating offshore wind turbine in pitch free-decay motion. The simulations are carried out with both linear and dynamic mooring models. The linear and quadratic damping coefficients of the semi-submersible are derived from the pitch motion data. In the verification study, a least-squares method using the observed order of convergence in combination with a data quality measure for different spatial and temporal refinement is applied to estimate the discretization errors. The numerical uncertainty is quantified by applying a safety factor to the summation of numerical errors. The numerical solutions are validated against the experimental measurements obtained from wave tank test of OC5-DeepCWind semi-submersible. Validation is achieved in the pitch natural period and the linear damping coefficient within the level of validation uncertainty. While the numerical simulation under-predicts the quadratic damping coefficient. A guideline is provided for verification and validation study of a CFD code application for floating marine structures under decay tests. Highlights: Evaluation of iterative uncertainty from all sources. Estimation of spatial and temporal discretization uncertainty in flow solver and mooring solver. Validation against model test data. Guideline for CFD simulation of free decay of floating marine structures.